MANAGEMENT OF INNOVATIVE PROJECTS IN THE ENGINEERING COMPANIES - Y. Aleksandrov (Вестник университета)
The article considers the problems of project management in engineering companies, including the stage of planning, organization and control over all matters in the continuous process of development of the project and the fulfillment of its purposes. It is shown that the use of methods of project management enables you to more effectively implement long-running implementation of decisions involving a significant number of units with different subordination.